Continuously fabricated nano/micro aligned fiber based waterproof and breathable fabric triboelectric nanogenerators for self-powered sensing systems. (15th December 2022) - Zhou, Mengjuan; Xu, Fan; Ma, Liyun; Luo, Qingliang; Ma, Wanwan; Wang, Rongwu; Lan, Chuntao; Pu, Xiong; Qin, Xiaohong
Abstract: The electronic textile has been evolving into a multifunctional flexible electronics platform. However, due to processing methods, e.g., coating, the fabric is endowed with electronic functionality while weakening its original performances. Thus, there is still a long way for electronic fabrics. Here, a nano/micro core-sheath yarn-based waterproof and breathable fabric triboelectric nanogenerator (CSYF TENG) is continuously fabricated for energy harvesting, self-powered humidity, and subtle force sensing systems. Different from coated yarns, our uniaxially aligned CSYs with ordered nanofibers tightly wrapping around the conductive fibers are manufactured via a one-step conjugate electrospinning technique. Owing to the hierarchical structure and tremendous specific surface areas, CSYF TENGs exhibit unparalleled electrical outputs with excellent durability and biomechanical pressure sensitivity, demonstrating superior comfortability, i.e., waterproof property, breathability, and flexibility, without sacrificing fabric's original properties. Furthermore, based on the micro/nano radial expansion fiber-based fabric architecture, the excellent humidity management properties are manifested, resulting in a fast response (8 s)/recovery of electrical outputs toward humidity, making CSYF TENG an ideal self-powered humidity sensor. Besides, this TENG can be used as a bioenergy harvester, a self-powered tiny force sensor, and a fabric-based e -skin with excellent machine-washable and abrasion resistance properties. This work highlights the numerous applications of CSYs for wearable TENGs and self-powered electronic textiles. Graphical Abstract: Text: A nano/micro core-sheath yarn-based fabric TENG is continuously fabricated for energy harvesting and self-powered sensing systems. Owing to the hierarchical structure and tremendous specific surface areas, CSYF TENGs exhibit unparalleled electrical output with excellent durability performance, high-pressure sensitivity, superior comfortability, waterproof property, breathability, flexibility, washability, abrasion resistance, and omnidirectional performances. Furthermore, based on the excellent humidity management performance of CSYF TENGs, self-powered humidity sensor, self-powered pressure sensor and electronic skins were developed. ga1 Highlights: A nano/micro core-sheath yarn based breathable fabric TENG is continuously fabricated. The hierarchical architecture strategy enables CSYF TENG as a subtle force sensor. Excellent humidity management makes CSYF TENG as an ideal humidity sensor. CSYF TENG exhibits superior comfortability, huge potential in wearable e-textile.